Equity-Based free channels assignment for secondary users in a cognitive radio network - Said Lakhal; Zouhair Guennoun (Institute of Advanced Engineering and Science, 2019)
The present paper addresses the equity issue among the secondary users in a cognitive radio network. After using a multi scheduler algorithm and a fairness metric namely Jain’s Equity Index; we enhance the equity between the secondary users’ transfer rates by 0.64 in average, relative to a previous work.